Hvem er forfatteren til Joachim Arentsehes “Krigsbog”? - Blosen, Hans (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2014)
One of the prized possessions of the Royal Library in Copenhagen, an expensively bound composite volume of seven different German-language writings on the art and legality of war printed in Copenhagen in 1578 by Lorentz Benedicht for Frederik II, is usually called Joachim Arentsehe’s “War Book”. However, the title pages assign only parts 2 and 4-7 to Arentsehe, while for parts 1 and 3 no author is named. The very extensive part 1, opening with woodcuts of the King’s portrait and the National Arms and containing numerous hand-coloured illustrations, is evidently the main work of the volume. Its author came to light in 2001 when German historian Rainer Leng, as part of a systematic investigation into the late medieval German “Büchsenmeisterbücher”, published Franz Helm’s “Buch von den probierten Künsten”, one of the most thorough and richly transmitted works on the art of war of the whole of the sixteenth century, which he wrote in around 1530. It is Helm’s book which comprises the main section of Frederik II’s “War Book”. Leng was unaware of Benedicht’s anonymous printed edition, and in Denmark the assumption of Arentsehe’s authorship continued to hold a veil over the true origins of the work, until a detailed comparison showed the two to be identical. While, in Germany, Helm’s work was transmitted only in manuscript for some 100 years, and was first printed in 1625, Benedicht’s Copenhagen printing dates from some 50 years earlier. The reason why transmittance was dominated by manuscripts is presumably both the desire to make the book’s content seem secret knowledge and the desire to give it an aura of exclusivity, such as more properly belongs to an illustrated manuscript than to a printed version. However, the same exclusivity was achieved by Benedicht’s printed work through the perfection of its craftsmanship, its illustrations and by the fact that it was produced in one copy only, for the use of the King.